Impact of COVID‐19 pandemic on cancer surgery: Patient's perspective. Issue 5 (16th February 2021) - Rajan, Shiv; Akhtar, Naseem; Tripathi, Abhilasha; Kumar, Vijay; Chaturvedi, Arun; Mishra, Prabhaker; Sharma, Sonali; Misra, Sanjeev; Gupta, Sameer; Singh, Mohit
Abstract: Background: Coronavirus disease 2019 (COVID‐19) has impacted cancer care globally. The aim of this study is to analyze the impact of COVID‐19 on cancer healthcare from the perspective of patients with cancer. Methods: A cross‐sectional survey was conducted between June 19, 2020, to August 7, 2020, using a questionnaire designed by patients awaiting cancer surgery. We examined the impact of COVID‐19 on five domains (financial status, healthcare access, stress, anxiety, and depression) and their relationship with various patient‐related variables. Factors likely to determine the influence of COVID‐19 on patient care were analyzed. Results: A significant adverse impact was noted in all five domains ( p  =  < 0.05), with the maximal impact felt in the domain of financial status followed by healthcare access. Patients with income levels of INR < 35 K (adjusted odds ratio [AOR] = 1.61, p  < 0.05), and 35K‐ 100 K (AOR = 1.96, p  < 0.05), married patients (AOR = 3.30, p  < 0.05), and rural patients (AOR = 2.82, p  < 0.05) experienced the most adverse COVID‐19‐related impact. Conclusion: Delivering quality cancer care in low to middle‐income countries is a challenge even in normal times. During this pandemic, deficiencies in this fragile healthcare delivery system were exacerbated. Identification of vulnerable groups of patients and strategic utilization of available resources becomes even more important during global catastrophes, such as the current COVID‐19 pandemic. Further work is required in these avenues to not only address the current pandemic but also any potential future crises.